Using the Power of Junctional Adhesion Molecules Combined with the Target of CAR-T to Inhibit Cancer Proliferation, Metastasis and Eradicate Tumors - Christopher Mendoza; Dario Mizrachi (Biomedicines, 2022)
Decades of evidence suggest that alterations in the adhesion properties of neoplastic cells endow them with an invasive and migratory phenotype. Tight junctions (TJs) are present in endothelial and epithelial cells. Tumors arise from such tissues, thus, the role of TJ proteins in the tumor microenvironment is highly relevant. In the TJ, junctional adhesion molecules (JAM) play a key role in assembly of the TJ and control of cell–cell adhesion. Reprogramming of immune cells using chimeric antigen receptors (CAR) to allow for target recognition and eradication of tumors is an FDA approved therapy. The best-studied CAR-T cells recognize CD19, a B-cell surface molecule. CD19 is not a unique marker for tumors, liquid or solid. To address this limitation, we developed a biologic containing three domains: (1) pH-low-insertion peptide (pHLIP), which recognizes the low pH of the cancer cells, leading to the insertion of the peptide into the plasma membrane. (2) An extracellular domain of JAM proteins that fosters cell–cell interactions. (3) CD19 to be targeted by CAR-T cells. Our modular design only targets cancer cells and when coupled with anti-CD19 CAR-T cells, it decreases proliferation and metastasis in at least two cancer cell lines.